Antioxidant Profiling and GC-MS Analysis of Active Subfractions from Jasminum sambac L. Leaf Extract - Megananda Ristya Putri; Iswandi; Nuraini Harmastuti (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2026)
Jasmine leaves (Jasminum sambac L.) are known to contain phenolic and flavonoid compounds with antioxidant potential. This study evaluated the antioxidant activities of the ethanol extract, solvent fractions, and subfractions of jasmine leaves. It characterized the chemical profile of the most active subfraction using gas chromatography–mass spectrometry (GC–MS). Jasmine leaves were extracted by maceration using 96% ethanol and subsequently fractionated with n-hexane, ethyl acetate, and water. The ethyl acetate fraction, which exhibited the strongest antioxidant activity, was further separated by vacuum liquid chromatography to obtain subfractions. Antioxidant activity was determined using the DPPH method and expressed as IC₅₀ values. The most active subfraction was analyzed by GC–MS. The results showed that the ethyl acetate fraction had the lowest IC₅₀ among the solvent fractions, while subfraction 1 (SF1) exhibited the strongest antioxidant activity, with an IC₅₀ of 49.78 ppm, indicating strong activity. GC–MS analysis of the most active subfraction suggested the presence of antioxidant-related compound classes with tentative identification. These findings demonstrate that subfractionation enhances antioxidant activity and enriches antioxidant-related constituents in jasmine leaves, while highlighting the need for advanced analytical techniques to confirm compound identities.